Routing Schemes for Wireless ATM Networks - Oudah, Ali A. (SERSC, 2014)
In this paper, the Wireless ATM rerouting procedures are analyzed and categorized based on a standard network topology, derived from the Wireless ATM reference model. A new operational concept for a mobile ATM network called Mobile Network Architecture based on Virtual Paths (MNA VP), in which the network nodes are connected to each other via pre-established permanent virtual path connections with fixed capacity assignments is being proposed and described. Finally, the handover hysteresis concept is introduced and a hysteresis gain is defined and calculated as the factor by which the handover rate is reduced through the use of the hysteresis.